Distribution of Pressure Fluctuations in a Prototype Pump Turbine at Pump Mode. (11th February 2014) - Sun, Yuekun; Zuo, Zhigang; Liu, Shuhong; Liu, Jintao; Wu, Yulin
Abstract : Pressure fluctuations are very important characteristics in pump turbine's operation. Many researches have focused on the characteristics (amplitude and frequencies) of pressure fluctuations at specific locations, but little researches mentioned the distribution of pressure fluctuations in a pump turbine. In this paper, 3D numerical simulations using S S T  k - ω turbulence model were carried out to predict the pressure fluctuations distribution in a prototype pump turbine at pump mode. Three operating points with different mass flow rates and different guide vanes' openings were simulated. The numerical results show how pressure fluctuations at blade passing frequency (BPF) and its harmonics vary along the whole flow path direction, as well as along the circumferential direction. BPF is the first dominant frequency in vaneless space. Pressure fluctuation component at this frequency rapidly decays towards upstream (to draft tube) and downstream (to spiral casing). In contrast, pressure fluctuations component at 3BPF spreads to upstream and downstream with almost constant amplitude. Amplitude and frequencies of pressure fluctuations also vary along different circumferential locations in vaneless space. When the mass flow and guide vanes' opening are different, the distribution of pressure fluctuations along the two directions is different basically.